PENGARSIPAN OBAT TRADISIONAL SUKU BATAK KARO DI SUMATERA UTARA: Array - Christy Lavenia; Nafa Febrianti Mutia Dewi (Jurnal Kearsipan, 2020)
Traditional medicine in Indonesia has been used for thousands of years, biodiversity is an opportunity for the development of traditional medicine. One of the ethnic groups that still use and develop traditional medicine is the Batak Karo. Some traditional medicines of the Batak Karo ethnic group such as parem, tawar, and massage oil. The medicines are inherited from generation to generation so that the archive of traditional medicine is still very lacking, even its use in public is difficult. Community Archives (AK) can be empowered to do archiving with protection and preservation of traditional medicine. Documentation of traditional medicine using AK is evidence that these traditional medicines belong to the Karo Batak. In addition, well-managed traditional medicine can facilitate its publication through archival networks and traditional medicine is disseminated as traditional knowledge. Publication of traditional medicine is expected to be able to maintain the existence of traditional knowledge, especially traditional medicine from generation to generation.